Moderasi Beragama dalam Perspektif Al-Qur’an dan Hadis - Anwar, Syaeful; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Moderation is a way of looking at a person's view of an event they are facing or currently experiencing. In the midst of modernization today, as pluralistic creatures, we must always have a wise attitude in viewing differences, whether in terms of religion, culture, economics, and so on. Meanwhile, the current democratic system considers that everything must be seen from various perspectives and views that are based on "freedom" in opinion, thinking and acting in all matters, however our nation is a religious nation, a cultural and different nation. different tribes, so that what becomes a "conflict" in a certain area will be quickly resolved again, with the uniqueness and diversity that exists.The current phenomenon of democracy, which is increasingly chaotic, especially in cyberspace, makes it easy for anyone to access and express their opinions clearly, even though it seems to ignore existing ethics and culture. However, from the perspective of any religion, this is not recommended because it violates applicable religious values ​​and norms. So that we as human beings who think logically and are educated should not always follow desires and wishes based on passion and conscience which leads us to things that bring us down.